Consumption of macrolides, lincosamides and streptogramins in the community, European Union/European Economic Area, 1997–2017. (1st August 2021) - Adriaenssens, Niels; Bruyndonckx, Robin; Versporten, Ann; Hens, Niel; Monnet, Dominique L; Molenberghs, Geert; Goossens, Herman; Weist, Klaus; Coenen, Samuel; ,
Abstract: Objectives: Data on the consumption of macrolides, lincosamides and streptogramins (MLS) in the community were collected from 30 EU/European Economic Area (EEA) countries over two decades. This article reviews temporal trends, seasonal variation, presence of change-points and changes in composition of the main subgroups of MLS. Methods: For the period 1997–2017, data on consumption of MLS, i.e. ATC group J01F, in the community and aggregated at the level of the active substance, were collected using the WHO ATC/DDD methodology (ATC/DDD index 2019). Consumption was expressed in DDD per 1000 inhabitants per day and in packages per 1000 inhabitants per day. Consumption of MLS was analysed and presented as trends, seasonal variation, presence of change-points and compositional changes, using a classification based on mean plasma elimination half-life for macrolides. Results: In 2017, consumption of MLS in the community expressed in DDD per 1000 inhabitants per day varied by a factor of 13 between countries with the highest (Greece) and the lowest (Sweden) consumption. Consumption of MLS did not change significantly up to 2003, after which it significantly increased up to 2007. No significant change was observed after 2007. Consumption of MLS showed high seasonal variation. The proportional consumption of long-acting macrolides significantly increased over time compared with that of intermediate-acting macrolides, and proportional consumption of the latter increased compared with that of short-acting macrolides. Conclusions: Consumption of MLS did not change significantly over time during 2007–2017, while the proportional consumption of long-acting macrolides increased. Seasonal variation remained high, which suggests that MLS are still prescribed inappropriately in many countries.